Hypofractionated radiotherapy for localized prostate cancer - Höcht, Stefan; Wenz, Frederik (Strahlentherapie und Onkologie, 2017)
Aim: This article gives an overview on the current status of hypofractionated radiotherapy in the treatment of prostate cancer with a special focus on the applicability in routine use. Methods: Based on a recently published systematic review the German Society of Radiation Oncology (DEGRO) expert panel added additional information that has become available since then and assessed the validity of the information on outcome parameters especially with respect to long-term toxicity and long-term disease control. Results: Several large-scale trials on moderate hypofractionation with single doses from 2.4-3.4 Gy have recently finished recruiting or have published first results suggestive of equivalent outcomes although there might be a trend for increased short-term and possibly even long-term toxicity. Large phase 3 trials on extreme hypofractionation with single doses above 4.0 Gy are lacking and only very few prospective trials have follow-up periods covering more than just 2-3 years. Conclusion: Until the results on long-term follow-up of several well-designed phase 3 trials become available, moderate hypofractionation should not be used in routine practice without special precautions and without adherence to the highest quality standards and evidence-based dose fractionation regimens. Extreme hypofractionation should be restricted to prospective clinical trials.
First Online: 14 September 2016
Gesehen am 13.07.2018